2020
DOI: 10.1097/sla.0000000000004701
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial Examining the Impact of an Anorectal Surgery Multimodal Enhanced Recovery Program on Opioid Use

Abstract: Background: Anorectal cases may be a common gateway to the opioid epidemic. Opioid reduction is inherent in enhanced recovery after surgery (ERAS) protocols, but little work has evaluated ERAS in these cases. Objective: To determine if ERAS could reduce postoperative opioid utilization in ambulatory anorectal surgery without sacrificing patient pain or satisfaction. Methods: A randomized controlled trial assigned ambulatory anorectal patients to ERAS (experimental) or routine care (surgeon's choice) for pain m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Seu et al [17] observed similar findings via a 36% reduction in total inpatient opioid use and a 57% reduction in total outpatient opioid use during bariatric surgery when ERAS protocols were implemented. Furthermore, a randomized control trial on ambulatory anorectal surgery found that an ERAS protocol reduced opioid use and healthcare utilization with no difference in pain or patient satisfaction [18]. As the highest number of postoperative opioid prescriptions are written by surgical specialists [19], the above findings also highlight the importance of involving surgeons in the shared responsibility of ensuring implementation and efficacy of ERAS protocols and other MMA programs.…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 97%
“…Seu et al [17] observed similar findings via a 36% reduction in total inpatient opioid use and a 57% reduction in total outpatient opioid use during bariatric surgery when ERAS protocols were implemented. Furthermore, a randomized control trial on ambulatory anorectal surgery found that an ERAS protocol reduced opioid use and healthcare utilization with no difference in pain or patient satisfaction [18]. As the highest number of postoperative opioid prescriptions are written by surgical specialists [19], the above findings also highlight the importance of involving surgeons in the shared responsibility of ensuring implementation and efficacy of ERAS protocols and other MMA programs.…”
Section: Enhanced Recovery After Surgerymentioning
confidence: 97%
“…Patients with perianal disorders seek treatment including surgical interventions for aggravated symptoms [2]. Most patients experience mild to moderate pain during the perioperative period of perianal surgery, whereas some experience severe postoperative pain [3,4]. Postoperative pain is not only a common cause of delayed discharge but also one of the leading reasons for readmission of patients after perianal surgery [5,6].…”
Section: Introductionmentioning
confidence: 99%